2019
DOI: 10.1002/pat.4737
|View full text |Cite
|
Sign up to set email alerts
|

Flame retardant and mechanism of vinyl ester resin modified by octaphenyl polyhedral oligomeric silsesquioxane

Abstract: Flamability is one of the major issues for utilization of bisphenol A-type vinyl ester resin (VER) polymeric composites in practical applications. The thermal stability and mechanical property of VER composites containing octaphenyl polyhedral oligomeric silsesquioxane (OPS) were investigated and discussed in detail. With increasing the mass ratio of OPS, the residues yield at 800°C and bending strength at break of the VER/OPS composites were enhanced, accompanied with the gradually decreased values of the pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The main pyrolysis product peaks of pure VER and VER‐3 are similar, including phenol derivatives/water (3586 cm −1 ), aliphatic components (2660–2860 cm −1 ), aromatic components (3010, 1504, and 670 cm −1 ), carbonyl components (1723 cm −1 ), ester/ether components (1153 cm −1 ), and CO (2178 cm −1 ). [ 31,32 ] With 3 wt% Li‐Ph‐POSS incorporation of the matrix, the pyrolysis product peaks have declined except for 3010, 1504 — , and 670 cm −1 . The reduction demonstrates that more decomposition products of the matrix remain in the condensed phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main pyrolysis product peaks of pure VER and VER‐3 are similar, including phenol derivatives/water (3586 cm −1 ), aliphatic components (2660–2860 cm −1 ), aromatic components (3010, 1504, and 670 cm −1 ), carbonyl components (1723 cm −1 ), ester/ether components (1153 cm −1 ), and CO (2178 cm −1 ). [ 31,32 ] With 3 wt% Li‐Ph‐POSS incorporation of the matrix, the pyrolysis product peaks have declined except for 3010, 1504 — , and 670 cm −1 . The reduction demonstrates that more decomposition products of the matrix remain in the condensed phase.…”
Section: Resultsmentioning
confidence: 99%
“…The Si 2p spectra (Figure 8D) reveal two silicon configurations, which are SiOSi/SiOC at 103.4 eV and CSi at 102.0 eV. [ 26,28,32,33 ] The Li 1s spectra (Figure 8E) are only one peak attributed to LiCO 3 . It is reported that LiCO 3 can promote the formation of char layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major pyrolysis gases detected in the decomposition process of VER systems are phenol derivatives/water (3650 cm −1 ), aromatic components (3072, 3033, 1603, 1506, 1335 cm −1 ), aliphatic components (2973, 2930 cm −1 ), ester or ether components (1752, 1256, 1176, 1126 cm −1 ) and CO 2 (2358 cm −1 ), which correspond well with the decomposition of VER matrix in the literature. 38 As shown in Fig. 10(A), the gas species changed when the flame retardants were added into VER.…”
Section: Analysis Of Volatile Pyrolysis Products Of Ver Systemsmentioning
confidence: 99%
“…[5][6][7] Nonetheless, some potential disturbances may occur and have an influence on the stabilization of the part weight. [8] Therefore, some researchers have adopted data analysis to achieve failure detection and maintenance prediction of injection molding machine. Pilla et al [9] use edge computing and cloud computing for machine learning by introducing the Industry 4.0 framework, to enable effective prediction and management of maintenance operations for injection molding equipment.…”
Section: Introductionmentioning
confidence: 99%